Aging Women, Living Poorer. (May 2014) - Torres, Stacy
Sociologist Stacy Torres examines why higher poverty rates persist among older women compared with older men and finds that women continue to face significant economic disadvantages in old age, partly due to a lifetime of unpaid, work-interrupting care giving responsibilities.